A New Efficient Method for solving Helmholtz and Coupled Helmholtz Equations Involving Local Fractional Operators - Kamil Jassim, Hassan; Ali Naser, Hasan; Kleef Jiheel, Alaa (University of Thi-Qar Journal of Science, 2019)
In this manuscript, we apply a new technique, namely local fractional Laplace variational iteration method (LFVITM) on Helmholtz and coupled Helmholtz equations to obtain the analytical approximate solutions. The iteration procedure is based on local fractional derivative operators (LFDOs). This method is the combined of the local fractional Laplace transform (LFLT) and variational iteration method (VIM). The method in general is easy to implement and yields good results. Illustrative examples are included to demonstrate the validity and applicability of the new technique.